The positive and negative significance of the star in the mesopotamian civilization: a semiotic study - Juhaena Hamid Hasani; Siti Rugayah Hj. Tibek; Ghassan Taha Yaseen; Eeman Muhammad Abbas (Institut Kajian Rantau Asia Barat, 2012)
This study deals with semiotic findings about the significance of the stars in its dual contradictory aspects, both the positive and the negative as found in the Mesopotamian civilization. Stars, in mid nights have been the means of guidance both on the land and the sea. People make use of them to determine the time (the day, the month etc), as well as the inference of knowledge through which the road map came into existence and widened the intellectual channels in reading fortunes, horoscopes and characterized as signs or benchmarks by which its consistent rhetorical practices became marketable among people until today. This study is quite different from the previous studies in the sense that it deals with two significant aspects which are: First; It focuses on the structural transformation of the significance of the star between two contradictory forms (the positive and the negative), beginning with the first culture dating back to the period of pre-history until the modern Babylonian age during which Mesopotamian civilization flourished. Moreover, this study attempts to present a modification and amendments on the findings of the previous researches,